Defect in ser46 phosphorylation of p53 protein: a resistance mechanism against p53 gene transfer in oral squamos cell carcinoma cells - Arief Ichwan, Solachuddin Jauhari; Ikeda, Masa-Aki (Japanese Association for Oral Biology, 2008)
Oral squamous cell carcinoma (SCC) shows frequent metastasis and recurrence, ultimately with a poor outcome. The long-term survival rates of patients with oral SCC have not significantly been improved. The p53 tumor suppressor gene is known to be one of the most commonly mutated genes in human cancers, including oral SCC. p53 gene replacement therapy to treat such cancers has become an intensive area of research. However, the introduction of wild-type p53 protein is unable to induce apoptosis in all tumor cases, at least in part, due to their resistance to exogenous p53. Recently, we reported that a defect in the phosphorylation of p53 protein at serine 46, which is critical for p53-mediated apoptosis, is responsible for the acquisition of resistance to p53 gene transfer in oral SCC cells. In this review, we focus on the regulation of Ser46 phosphorylation and discuss the contribution of its dysregulation to resistant mechanisms against p53 gene transfer in oral SCC.